Effectiveness of self-financed rotavirus vaccination in Ise City, Japan - Mitsue Ito; Masamune Higashigawa (Taylor & Francis Group, 2021)
In Japan, the herd immunity effect of rotavirus vaccine has not yet been proven. Here, we conducted active surveillance for hospitalization due to rotavirus acute gastroenteritis (AGE) among children under 5 years of age in pre-rotavirus vaccination years and self-financed rotavirus vaccination years to clarify the rotavirus vaccine effectiveness (VE) in reducing hospitalization rates. A time-series analysis showed that the monthly hospitalization rates observed after vaccine introduction were significantly lower than the forecasted hospitalization rates (p < .001, Mann-Whitney U test). In the third year after vaccine introduction, the hospitalization rate declined despite the low vaccination rate of 27-50% for the two preceding years. We estimated four types of VE, namely direct, indirect, total, and overall. The direct VE was calculated from the relative risk ratio of hospitalizations between vaccinated and unvaccinated children. The indirect VE was defined as the population-level effects of vaccination on children not receiving the vaccine. The total VE was defined as the combination of the direct and indirect VE on children receiving the vaccine. The overall VE was determined by the weighted average of indirect VE on the children not receiving the vaccine and the total VE on the children receiving the vaccine. The direct, indirect, total, and overall VE values were calculated as 82% (95% confidence interval, 52-93), 70% (51-82), 95% (87-98), and 86% (77-91), respectively. The high values of indirect, total, and overall VE indicate that the rotavirus vaccine produces a herd immunity effect.